5G as Geopolitical Power Struggle: The New Neutral Approach of Balance and Safety in Technology Controlled World Explained through a Case Study of Serbia - Bojić, Ljubiša; Djukanović, Dragan; Nikolić, Nemanja (NBP. Nauka, bezbednosti, policija, 2022)
5G is a critical sensitive technology that could endanger public safety. Recent progress of Huawei in the number of patents relating to 5G caused a trade war over the issue, with multiple actions from the US, including restrictions towards Chinese companies. This paper seeks to explore the issue of 5G around global security and the struggle for geopolitical dominance. Identified gap in the literature is related to the question if there is a safe side in terms of choices that countries make around 5G vendors. Earlier studies have not considered this question appropriately in a comprehensive way, because of one sided look and policy approach. The second question attempts to find the best solution for countries to escape dominance of 5G vendors, ensure high safety and avoid potential hazards. To put 5G technology in context, we present geopolitical issues around a global information infrastructure, provide information into China’s 5G strategy and history of tech struggles between China and the US. We further present emerging geopolitical safety issues regarding 5G technology and elaborate Serbia’s geopolitical turmoil related to 5G. In conclusion we classify countries based on their position about this issue to the West, the East and the Neutral corpuses. The focus on Serbia and politics of 5G diversity is then examined to conclude that this geopolitical position of 5G Neutrality could be beneficial for the balanced World in which new technologies will be base for multilateral dominance. This paper is limited in technical and legal analysis of the issue. Further research should propose encryption and quality control standards together with legal framework, to ensure diversity in social interest.